Population bottleneck triggering millennial-scale morphospace shifts in endemic thermal-spring melanopsids - Neubauer, Thomas A. (Palaeogeogr Palaeoclimatol Palaeoecol, 2014)
For more than hundred years the thermal spring-fed Lake Pețea near Oradea, Romania, was studied for its highly endemic subfossil and recent fauna and flora. One point of focus was the species lineage of the melanopsid gastropod Microcolpia parreyssii, which exhibited a tremendous diversity of shapes during the earlier Holocene. As a consequence many new species, subspecies, and variety-names have been introduced over time, trying to categorize this overwhelming variability. In contrast to the varied subfossil assemblage, only a single phenotype is present today. We critically review the apparent “speciation event” implied by the taxonomy, based on the presently available information and new data from morphometric analyses of shell outlines and oxygen and carbon isotope data. This synthesis shows that one turning point in morphological evolution coincides with high accumulation of peaty deposits during a short time interval of maximally a few thousand years. The formation of a small, highly eutrophic swamp with increased input of organic matter marginalized the melanopsids and reduced population size. The presented data make natural selection as the dominating force unlikely but rather indicates genetic drift following a bottleneck effect induced by the environmental changes. This claim contrasts the “obvious trend” and shows that great morphological variability has to be carefully and objectively evaluated in order to allow sound interpretations of the underlying mechanisms.